Tajemnice warsztatu twórców polskiej poezji mnemotechnicznej (od XIV do XVIII wieku) na przykładzie akrostychu i chronostychu - Wich, Urszula (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The artice treats on two genres of mnemotechnical poetry: acrostichon and chronostichon, which belong also to poesis artificiosa current. There have been done genological analisis of this two genres, and there also have been showed their development on century time frame (since 14th to 18th century). This two genres of Old Polish poetry appeared in the first decade of the 14th century and there have been showed several variants of each genre and also their development far to 18th century. The article deals with all the availabe in print works, both in Polish and Latin, which belong to this genres. It was noticed that acrostichon had been useful and therefore was often practised in love poetry. The use of this genre was a good method of paying compliments to the beautiful woman. It was also a manifestation of baroque poetry with the use of puns and suprising changes of meaning.